Trend Analysis of Temperature and Humidity in Kwara State, Nigeria - Adedapo, Adeniyi (Journal of Environmental Geography, 2020)
This paper examines the trend analysis of temperature and relative humidity in Kwara State. Climatic data on annual mean temperature (minimum and maximum) and relative humidity for 40 years (1978-2017) were collected from Nigerian Meteorological Agency (NIMET) Ilorin. Semi-Average method, Mann- Kendull statistics and regression method were used to analyse the trend in temperature and relative humidity. The Standardized Anomaly Index (SAI) was also used to examine the changes in temperature and humidity over the period of 1978-2017. The result of the analysis indicates that temperature (minimum and maximum) and relative humidity exhibit an upward trend. This implies that temperature and relative humidity increase over the period of 1978-2017. The Mann-Kendull statistics values show that there is no significant difference in the values of temperature (minimum and maximum) and relative humidity. The result of the Standardized Anomaly Index (SAI) also revealed that the values of temperature and humidity fluctuated around the long –term mean. About 50% of the annual average relative humidity falls above the long term average while 40% of the annual mean maximum temperature falls above the long term average. It can therefore, be deduced that there is the possibility of increment in the values of temperature and relative humidity which could cause a serious challenge to human health and climate change. The study therefore, suggests that increase and fluctuations in temperature and relative humidity should be a critical factor in designing strategies to mitigate the effect of climate change on the environment and human health.